Loss of Müller cell glutamine synthetase immunoreactivity is associated with neuronal changes in late-stage retinal degeneration - Reynisson, Hallur; Kalloniatis, Michael; Fletcher, Erica L.; Shivdasani, Mohit N.; Nivison-Smith, Lisa (Frontiers in Neuroanatomy, 2023)
A hallmark of photoreceptor degenerations is progressive, aberrant remodelling of the surviving retinal neurons and glia following photoreceptor loss. The exact relationship between neurons and glia remodelling in this late stage of retinal degeneration however is unclear. In this study, we assessed this by examining Müller cell dysfunction via glutamine synthetase immunoreactivity and its spatial association with retinal neuron subpopulations through various cell markers. We found that glutamine synthetase immunoreactivity was progressively lost as a function of age in late-stage degeneration in the rd1 mouse retina (P150 – P536). Immunoreactivity of other Müller cell markers however was unaffected in areas of reduced glutamine synthetase labelling suggesting Müller cells were still present in these regions. This loss appeared to affect specific neuronal populations including Type 2, Type 8, and rod bipolar cells, as well as AII amacrine cells based on reduced recoverin, protein kinase Cα and parvalbumin immunoreactivity respectively. The number of cell nuclei within regions of low glutamine synthetase immunoreactivity was also reduced suggesting possible neuronal loss rather than simply reduced cell marker immunoreactivity. These findings further support a strong interplay between glia-neuronal alterations in late-stage degeneration and highlight a need for future studies and consideration in intervention development.